An Interaction Design for Improving User Experience with the Health Protocol of COVID-19 Pandemic in Indonesia - Silvira Trijayati; Jerry Kurniawan Tumewah; Arya Harditya (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2022)
COVID-19 is a disease that has spread throughout the world and is transmitted through inhalation or contact with droplets of infected people. The Indonesian Government has established a health protocol to reduce the spread of COVID-19, which is checking the body temperature of visitors at public places. The officers' representatives from public places are mobilized to check the body temperature of the visitors by bringing the thermometer closer to the forehead or hand of the visitors. This paper aims to design a contactless thermometer using an Arduino Uno by adding an interactive design and light installation. It aims to enhance the user-experience rather the design idea itself. The thermometer will move a mechanical flower adjusted by the temperature measurement with this product design.